2022
DOI: 10.3390/bios12040252
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Flexible Electrochemical Biosensors to Monitor Alcohol in Sweat

Abstract: The continued focus on improving the quality of human life has encouraged the development of increasingly efficient, durable, and cost-effective products in healthcare. Over the last decade, there has been substantial development in the field of technical and interactive textiles that combine expertise in electronics, biology, chemistry, and physics. Most recently, the creation of textile biosensors capable of quantifying biometric data in biological fluids is being studied, to detect a specific disease or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Electrochemical techniques can be classified as amperometry, potentiometry, and coulometry. Amperometry measures the current in response to applying a constant or pulsed potential ( Costa et al, 2022 ). Voltammetry, a subclass of amperometry, is the most applied technique in diagnostics and environmental analysis, particularly cyclic voltammetry (CV), differential pulse voltammetry (DPV), and square wave voltammetry (SWV), because of its simplicity and speed ( Magar et al, 2021 ).…”
Section: Electrochemical Signal Amplification Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical techniques can be classified as amperometry, potentiometry, and coulometry. Amperometry measures the current in response to applying a constant or pulsed potential ( Costa et al, 2022 ). Voltammetry, a subclass of amperometry, is the most applied technique in diagnostics and environmental analysis, particularly cyclic voltammetry (CV), differential pulse voltammetry (DPV), and square wave voltammetry (SWV), because of its simplicity and speed ( Magar et al, 2021 ).…”
Section: Electrochemical Signal Amplification Strategiesmentioning
confidence: 99%
“…In a reversible system, more intense signals are obtained using SWV, increasing the sensitivity compared to other voltammetric techniques. SWV is more rapid and sensitive than DPV due to the absence of interference caused by the background current ( Costa et al, 2022 ).…”
Section: Electrochemical Signal Amplification Strategiesmentioning
confidence: 99%
“…Furthermore, it has been reported that some neurotransmitters have further roles (beyond simple intrasynaptic signal transmission), including brain functioning [ 30 , 124 ]. Additionally, by focusing on its inherent function for monitoring, electrochemical sensors can be applied to clinical investigations, along with the flexible/wearable/implantable electronic devices that have recently begun to attract attention in the biosensor field, enabling the practical real-time monitoring of neurotransmitter-related diseases in patients [ 125 , 126 , 127 ]. Electrochemical nanobiosensors can also be used as a core component in the development of probe-free electronic devices capable of performing sensing functions such as the electronic nose/tongue, for the monitoring of various targets, including neurotransmitters [ 128 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Most of the review articles are focused only on the development of wearable sensor electrodes and the related technologies for wireless data transmission [ 6 , 7 , 8 , 9 , 10 ]. Some articles are oriented towards the detection of a single metabolite [ 11 ], while some are focused on the detection of sweat metabolites by a particular type of nanomaterial [ 12 ]. However, there is a lack of review articles for accumulatively streamlined comprehensive discussion regarding the basics of enzymatic as well as non-enzymatic sensor development for the electrochemical sensing of sweat metabolites followed by its integration with flexible substrates for fabricating wearable devices and an in-depth sensing mechanism under one umbrella.…”
Section: Introductionmentioning
confidence: 99%